Image Segmentation Performance using Deeplabv3+ with Resnet-50 on Autism Facial Classification - Melinda Melinda; Hurriyatul Aqif; Junidar Junidar; Maulisa Oktiana; Nurlida Basir; Afdhal Afdhal; Zulfan Zainal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2024)
Indexed by MyCite